A CONSTRUÇÃO DO HUMOR NO INSTAGRAM: UMA ANÁLISE TECNODISCURSIVA DAS TIRAS E DOS COMENTÁRIOS CONVERSACIONAIS - Santos, Amalia Pratte (2020)
The research work developed aims to analyze the construction of humor in the digital environment. The corpus, composed of comic strips posts by the author Carlos Ruas and its comments, was selected on the digital platform Instagram within the content of U